2019
DOI: 10.1142/s0217984919500775
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of neon soft X-ray yield in a low-energy dense plasma focus device

Abstract: The Lee model code is used in numerical experiments for characterizing and optimizing neon soft X-ray (Ysxr) yield of UNU/ICTP PFF machine operated at 14 kV and 30 µF. The neon Ysxr yield of the dense plasma focus device is enhanced by reducing static inductance (L0) and anode length (z0) along with increasing anode radius (a) and cathode radius (b), keeping their ratio (c = b/a) constant at 3.368. At the optimum combination of the electrodes geometry and static inductance, the maximum computed value of neon Y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is good to compare the SPF device with cylindrical plasma focus devices in terms of soft x-ray yield efficiency. The following soft x-ray efficiencies in terms of the bank energy are obtained from cylindrical plasma focus devices: NX1 (4.5%) [45], NX2 (1.2%) [46], UNU/ICTF PFF (1.9%) [32], PF-SY1 (0.92%) [33,53], AECS-PF2 (0.75%) [34], 2.2 kJ PF (0.2%) [47], 3 kJ PF (0.1%) [48], 3.3 kJ PF (0.25%) [49], 1.8 kJ PF (1.55%) [17]. Comparing the efficiency of the SPF with cylindrical designs in terms of soft x-ray yield, we can see that these devices have similar efficiency of the soft x-ray yield.…”
Section: Soft X-ray Yield Optimization For Various Neon Gas Pressures...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is good to compare the SPF device with cylindrical plasma focus devices in terms of soft x-ray yield efficiency. The following soft x-ray efficiencies in terms of the bank energy are obtained from cylindrical plasma focus devices: NX1 (4.5%) [45], NX2 (1.2%) [46], UNU/ICTF PFF (1.9%) [32], PF-SY1 (0.92%) [33,53], AECS-PF2 (0.75%) [34], 2.2 kJ PF (0.2%) [47], 3 kJ PF (0.1%) [48], 3.3 kJ PF (0.25%) [49], 1.8 kJ PF (1.55%) [17]. Comparing the efficiency of the SPF with cylindrical designs in terms of soft x-ray yield, we can see that these devices have similar efficiency of the soft x-ray yield.…”
Section: Soft X-ray Yield Optimization For Various Neon Gas Pressures...mentioning
confidence: 99%
“…It is found that decreasing cylindrical anode length improves soft x-ray yield but using tapered anode did not improve soft x-ray yield in the device [30]. Static inductance, anode length, anode radius, and gas pressure are also investigated for neon soft x-ray yield optimization in plasma focus [31][32][33][34]. These studies show that there is an optimum gas pressure as well as an optimum static inductance when the optimum anode length and anode radius are used to increase soft x-ray yield in plasma focus.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the SXR yield in the cylindrical PF devices, optimization of the device parameters is necessary. For this purpose, cylindrical PF devices are investigated for different static inductances, anode length and radius, capacitor bank, and cathode radius [17][18][19]. After optimizing these parameters, SXR yield is studied with respect to gas pressure and it is found that there is also an optimum gas pressure point for SXR yield in cylindrical PF.…”
Section: Introductionmentioning
confidence: 99%